Conocimiento de las cuidadoras sobre signos y síntomas de alarma en iras y edad y sus consecuencias en la salud de los niños menores de 5 años que acuden al Subcentro de Salud de San Gerardo periodo de enero-julio del 2011. - Gadvay Gusqui, Marcia Natali (2011)
The present research has been carried out to determine the knowledge and attitude ofateenager mother about the care of the newborn baby in the Gynecology Service of the“Hospital Provincial General Docente de Riobamba” from January to July 2010. The inductive-deductive and analytic methods were used in this study. A sample of 184teenagermothers was chosen from 355. Surveys and field trips were applied togatherinformation and established conclusions. The main results according to the objectives determine that the knowledge and attitude of the teenager mothers are not adequate to make sure an optimum care for the newborn baby. The following problems have been found: mothers are afraid when they hold their children, at time of bathing because they might fall down. There is a high rate of teenager mother ignorance and it is reflected in the rejection or indifference to their children.